Penyimpangan Seksual dalam Sastra Indonesia Mutakhir - - Sulaiman (Widyagogik)
This research is to desribe gender unequality which happens to woman characters in late Indonesian literature. Women are identified as weak ethnic, irrational, full of emotion, and to be the object of violence. The type of this research is qualitative with gynesis approach. The technique of data collection which is applied is documentation. The data, then, is analyzed through descriptive analysis and content analysis with three stages, which are: (1) identification, (2) comparation, and (3) application. From the analysis, it is found that in late Indonesian literature written by woman-writer, there are sexual divergences. The forms of sexual divergences include sexual abuse, sexual insulting and love dishonesty, gay and lesbian, and sexual violation against women.